PELAKSANAAN E-GOVERNMENT DI KANTOR IMIGRASI KELAS IA KOTA PEKANBARU TAHUN 2014 - Vergien, Gianio; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Development of E-Government is an attempt to develop the implementation of governance through the use of electronic media to improve the quality of public services. The purpose electronic government is to improve citizens' access to public services, government services, increasing access to sources of information held by the government, to handle public complaints and service quality equation that can be enjoyed by all citizens. The use of information systems for the purpose so that the service could be faster, but not all people know the existence of such passport information system. People who are or will make a passport, passport information system to use it. The purpose of this study was to analyze the implementation of E-Government in the passport at the Immigration Office of Pekanbaru. In this study, the concept used refers to the Electronic Government or the E-Government. This study uses descriptive study using a qualitative method approach. In the data collection researchers use interviewing techniques and documentation. The results of this study can be concluded that the implementation of E-Government in the passport at the Immigration Office Class IA Pekanbaru City has not been done well it turned out for a passport online just for formality data only applicant community still fill your data manually at the Immigration Office. For that is expected. The need for data updated regularly on the website of the Immigration Office Class IA Pekanbaru City so there is something new going on, so many attract people to access it. because such reforms are indispensable additions website operator to be fast in responding to any complaints society in the process of interaction.Keywords: Implementation, e-Government, Passport Online